Upaya Meningkatkan Hasil Belajar Pada Muatan Mata Pelajaran PPKn Tema 1 Subtema 1 Pada Materi Nilai-Nilai Pancasila Dalam Kehidupan Sehari-Hari Menggunakan Media Gambar Berbasis Powerpoint Pada Kelas V SDN 3 Socah - Ahmaddah Nur Alfiatuz Zakiyah; Agung Setyawan (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research is based on the researcher's observations of the value of learning outcomes in PPKn subjects, especially on Pancasila material in fifth grade students at SDN Socah 3 where there are still students who do not really understand the application of Pancasila values in everyday life. An understanding of the application of Pancasila values also hopes that a spirit of nationalism and mutual cooperation, fairness, fulfilling obligations and being responsible and knowing the rights of peers and fellow human beings can be formed. In this case learning tends to lead to lecture methods without media so that students are quite unable to imagine examples which include the application of Pancasila values in everyday life, so the researchers conducted research on learning outcomes using powerpoint-based media images. After the research was carried out, the results were obtained in the form of increasing student learning outcomes in the PPKn lesson content material on Pancasila values. Powerpoint-based picture learning media can be regarded as one of the efforts to improve learning outcomes in Civics subject matter. Because it can help students to understand examples of applying Pancasila values in everyday life.